A New Experimental Technique for the Multi-axial Testing of Advanced High Strength Steel Sheets - Mohr, D.; Oswald, M. (Experimental mechanics, 2008)
This paper deals with the development of a new experimental technique for the multi-axial testing of flat sheets and its application to advanced high strength steels. In close analogy with the traditional tension-torsion test for bulk materials, the sheet material is subject to combined tension and shear loading. Using a custom-made dual actuator hydraulic testing machine, combinations of normal and tangential loading are applied to the boundaries of a flat sheet metal specimen. The specimen shape is optimized to provide uniform stress and strain fields within its gage section. Finite element simulations are carried out to verify the approximate formulas for the shear and normal stress components at the specimen center. The corresponding strain fields are determined from digital image correlation. Two test series are performed on a TRIP-assisted steel sheet. The experimental results demonstrate that this new experimental technique can be used to investigate the large deformation behavior of advanced high strength steel sheets. The evolution of the yield surface of the TRIP700 steel is determined for both radial and non-proportional loading paths.